Automated adherent cell elimination by a high-speed laser mediated by a light-responsive polymer. (December 2018) - Hayashi, Yohei; Matsumoto, Junichi; Kumagai, Shohei; Morishita, Kana; Xiang, Long; Kobori, Yohei; Hori, Seiji; Suzuki, Masami; Kanamori, Toshiyuki; Hotta, Kazuhiro; Sumaru, Kimio
Abstract Conventional cell handling and sorting methods require manual labor, which decreases both cell quality and quantity. To purify adherent cultured cells, cell purification technologies that are high throughput without dissociation and can be utilized in an on-demand manner are expected. Here, we developed a Laser-induced, Light-responsive-polymer-Activated, Cell Killing (LiLACK) system that enables high-speed and on-demand adherent cell sectioning and purification. This system employs a visible laser beam, which does not kill cells directly, but induces local heat production through thetrans -cis -trans photo-isomerization of azobenzene moieties. Using this system in each passage for sectioning, human induced pluripotent stem cells (hiPSCs) maintained their pluripotency and self-renewal during long-term culture. Furthermore, combined with deep machine-learning analysis on fluorescent and phase contrast images, a label-free and automatic cell processing system has been developed by eliminating unwanted spontaneously differentiated cells in undifferentiated hiPSC culture conditions. Yohei Hayashi et al. present a method for high-speed adherent cell sectioning and purification, along with a label-free and automatic cell processing system. They show that this method is able to section human induced pluripotent stem cells without losing pluripotency and viability.